2014
DOI: 10.4028/www.scientific.net/msf.783-786.1320
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Micropillars Combined with Chemical Surface Modifications – Independency of Actin Filament Spatial Distribution in Primary Osteoblasts

Abstract: Cell-biomaterial interactions are strongly affected by topographical and chemical surface characteristics. We found out earlier that geometric titanium (Ti) pillar structures in the micrometer range induce the cells to rearrange their actin cytoskeleton in short fibers solely on the top of the pillars. As a result, cell physiology was hampered concerning collagen I synthesis and spreading capacity. Furthermore, the position-dependent initial cell adhesion strength was declined near the edges. We asked whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As it was previously shown that biological cues are highly affected by topographical and biochemical changes of biomaterials, we experimentally determined the optimal L-HT-EphA2 concentration to be 5 μg mL –1 ( Figure S3A,B ). 93 It is also known that this family of tyrosine kinase proteins influences the actin cytoskeleton, affecting cell shape and adhesion. 94 Thus, we evaluated morphology, cell adhesion and spreading as a response to microenvironmental cues as an experimental readout.…”
Section: Resultsmentioning
confidence: 99%
“…As it was previously shown that biological cues are highly affected by topographical and biochemical changes of biomaterials, we experimentally determined the optimal L-HT-EphA2 concentration to be 5 μg mL –1 ( Figure S3A,B ). 93 It is also known that this family of tyrosine kinase proteins influences the actin cytoskeleton, affecting cell shape and adhesion. 94 Thus, we evaluated morphology, cell adhesion and spreading as a response to microenvironmental cues as an experimental readout.…”
Section: Resultsmentioning
confidence: 99%
“…In a general comparison with adherent human primary osteoblasts (HOB), the cell size of the MG-63 cells is up to six times smaller (Pautke et al, 2004) (Figure 6). Comparative studies of the MG-63 cells and HOB cells show no morphological differences regarding actin cytoskeleton organization on different topographically modified biomaterials (L€ uthen et al, 2005;Nebe et al, 2014).…”
Section: Morphologymentioning
confidence: 92%
“…The morphology of MG-63 cells growing in T 75 -culture flasks was quite similar over the passage range P5-P30 ( Figure 6A). Comparative studies of the MG-63 cells and HOB cells show no morphological differences regarding actin cytoskeleton organization on different topographically modified biomaterials (L€ uthen et al, 2005;Nebe et al, 2014). In a general comparison with adherent human primary osteoblasts (HOB), the cell size of the MG-63 cells is up to six times smaller (Pautke et al, 2004) (Figure 6).…”
Section: Morphologymentioning
confidence: 99%
“…The cell behavior on a biomaterial's surface is highly complex, and all the adhesion and signaling processes occurring at the interface are not fully understood until now. We revealed on a micro-pillared surface that osteoblasts developed an actin pattern adequate to the underlying surface -in mimicry fashion [1,2].…”
Section: Introductionmentioning
confidence: 94%